Job satisfaction of librarians in the federal university libraries in Nigeria/ Akanbi Mohammed Lawal and Basri Hassan - Mohammed Lawal, Akanbi; Hassan, Basri (Faculty of Information Management, Universiti Teknologi MARA, 2014)
Job satisfaction in librarianship has generally been perceived as a recent field of inquiry. The objectives are to determine the level of job satisfaction of librarians in the Federal University Libraries in Nigeria; determine the relationship between demographic variables and job satisfaction of librarians in the Federal University Libraries in Nigeria.; and to assess the relationship between job satisfaction of librarians in the Federal University Libraries in Nigeria and each of the following dimensions: (a) Condition of service, (b) Work environment, (c) Faculty status, {d) Unionism. This study was conducted among the Librarians in the selected Federal Universities across the Six Geopolitical Zones of Nigeria in order to determine the level of job satisfaction of librarians in the Federal University Libraries in Nigeria. The study also examined the demographic distribution of the respondents and assessed the level of job satisfaction based on some selected factors. The data collected were analyzed with reliable statistical tools, and conclusions were drawn based on the results obtained.